2016
DOI: 10.1002/sdtp.10830
|View full text |Cite
|
Sign up to set email alerts
|

P-6: Aqueous Precursor Based Solution-Processed Metal Oxide Semiconductor

Abstract: We investigated solution-processed oxide semiconductor films derived from various aqueous precursors. Findings show that the structure of metal complexes in the precursor solutions greatly affect decomposition temperature, impurity concentration, and more importantly, electrical performance. Also, facile redox reaction is demonstrated as one solution to remove impurities effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Oxide semiconductors are leading candidates for n-type transistors and microelectronics with high yield and uniformity. The high electron mobilities (>10 cm 2 V –1 s –1 ) of oxide FETs guarantee high sensitivity and high signal-to-noise ratio in biosensing. , Also, the high tolerance of structural defects and the minimized band tail trapping of oxide semiconductors allow oxide FETs to be processed at low temperature (<350 °C), and solution processing is a convenient and feasible approach to deposit high-performance oxide semiconductors on a large scale at low cost. Previously, aqueous metal oxide precursor solutions were used successfully to fabricate high-quality oxide semiconductors with field-effect mobility as high as 36.31 cm 2 V –1 s –1 , to fabricate conformal bioelectronics for wearable health-monitoring platforms and for sub-nanomolar neurotransmitter detection . Yet, to date, there have been limited systematic studies of oxide semiconductor-based Bio-FETs that addressed the fundamental factors of how the devices’ parameters affect their sensitivity or any detailed electrical characterization to estimate the lowest detectable charge.…”
mentioning
confidence: 99%
“…Oxide semiconductors are leading candidates for n-type transistors and microelectronics with high yield and uniformity. The high electron mobilities (>10 cm 2 V –1 s –1 ) of oxide FETs guarantee high sensitivity and high signal-to-noise ratio in biosensing. , Also, the high tolerance of structural defects and the minimized band tail trapping of oxide semiconductors allow oxide FETs to be processed at low temperature (<350 °C), and solution processing is a convenient and feasible approach to deposit high-performance oxide semiconductors on a large scale at low cost. Previously, aqueous metal oxide precursor solutions were used successfully to fabricate high-quality oxide semiconductors with field-effect mobility as high as 36.31 cm 2 V –1 s –1 , to fabricate conformal bioelectronics for wearable health-monitoring platforms and for sub-nanomolar neurotransmitter detection . Yet, to date, there have been limited systematic studies of oxide semiconductor-based Bio-FETs that addressed the fundamental factors of how the devices’ parameters affect their sensitivity or any detailed electrical characterization to estimate the lowest detectable charge.…”
mentioning
confidence: 99%
“…The image starts with the bottom doped Si substrate, which serves as the gate, 100 nm SiO2 gate oxide, IGZO as the semiconductor material, source M1 is a 25nm thick Molybdenum (Mo), M2 is 35 nm thick platinum (Pt), the source oxide is Al2O3 with the thickness at the top being 400nm, and the top drain contact is silver (Ag). The choice of metals was made due to the following considerations: As a rule of thumb, we 24 and others [31][32][33] found that post-metal-deposition annealing is required to reduce oxygen vacancies in the IGZO film. Also, it was reported that post-deposition annealing results in Molybdenum (Mo) being ohmic contact 34 and in platinum (Pt) becoming a Schottky contact 35 .…”
Section: Resultsmentioning
confidence: 99%